Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Konsumen UMKM (Studi Kasus: Djoin Cafe di Kecamatan Wonomulyo Kabupaten Polewali Mandar) - Putri Ayu Annisa; Mustari Mustari; Muh. Ihsan Said Ahmad; Nurdiana Nurdiana; Tuti Supatminingsih (Indonesian Journal of Pedagogical and Social Sciences, 2021)
The purpose of this study is to see whether price and service quality affect MSME customer satisfaction (a case study of djoin cafe in sub-district Wonomulyo, polewali mandar). price and service quality are independent variables in this study, while customer satisfaction is the dependent variable. This study uses descriptive quantitative techniques and survey research design. The population of this study consisted of 31,444 consumers who visited the Djoin Cafe which were taken from the 2020 data. The sampling technique in this study was the Non-propability Sampling technique, namely Accidental Sampling so that a sample of 111 consumers who visited the Djoin Cafe were obtained. The data feeder instrument uses observation, interviews and questionnaires. The data analysis technique uses multiple regression. The findings of this study indicate that: (1) price has a positive and significant effect on consumer satisfaction at Djoin cafe Wonomulyo District based on partial test results. (2) At Djoin Cafe in Wonomulyo Regency, service quality has a good and quite large influence on customer satisfaction. (3) The combination of price and service quality has a positive and significant effect on consumer satisfaction at Djoin cafe, Wonomulyo District, Polewali Mandar Regency.